The mechanism of gene targeting in human somatic cells. - Yinan Kan; Brian Ruis; Sherry Lin; Eric A Hendrickson (PLoS Genetics)
Gene targeting in human somatic cells is of importance because it can be used to either delineate the loss-of-function phenotype of a gene or correct a mutated gene back to wild-type. Both of these outcomes require a form of DNA double-strand break (DSB) repair known as homologous recombination (HR). The mechanism of HR leading to gene targeting, however, is not well understood in human cells. Here, we demonstrate that a two-end, ends-out HR intermediate is valid for human gene targeting. Furthermore, the resolution step of this intermediate occurs via the classic DSB repair model of HR while synthesis-dependent strand annealing and Holliday Junction dissolution are, at best, minor pathways. Moreover, and in contrast to other systems, the positions of Holliday Junction resolution are evenly distributed along the homology arms of the targeting vector. Most unexpectedly, we demonstrate that when a meganuclease is used to introduce a chromosomal DSB to augment gene targeting, the mechanism of gene targeting is inverted to an ends-in process. Finally, we demonstrate that the anti-recombination activity of mismatch repair is a significant impediment to gene targeting. These observations significantly advance our understanding of HR and gene targeting in human cells.